The Phenomenon of Artificial Intelligence Usage in News Writing Styles by Journalists of Bengkulu Ekspress.com - Kurnianti, Indah; Hadiprashada, Dhanurseto; Muzni, Nurlianti; Ceesay, Sait (Komunikator, 2024)
The emergence of Artificial Intelligence (AI) technology in journalism has brought about significant changes. Equipped with AI-powered tools, this technology has become an integral part of journalistic work, transforming the way news is processed. These advancements enable more efficient news production, increasing processing capacity in the digital era. This study examines the phenomenon of AI technology adoption in news writing by journalists at Bengkulu Ekspress.com. As AI evolves rapidly, many media outlets are integrating it to enhance efficiency in content creation. Employing a qualitative approach, this research incorporates in-depth interviews with several journalists and analyzes news content published on the Bengkulu Ekspress.com platform. The findings reveal that while AI contributes to various aspects of news writing, such as data processing and automated report generation, it does not entirely replace the role of journalists. Journalists retain primary control over key elements, including narrative construction, perspective, and the values conveyed in the news. Moreover, AI primarily functions as a tool to expedite workflows and improve information accuracy. Despite AI’s growing influence on the media industry, the role of human journalists as creators of news content remains indispensable.